SOSIALISASI PENGEMASAN PRODUK, LABEL PRODUK DAN PEMBUATAN LAPORAN KEUANGAN SEDERHANA BAGI PELAKU UMKM DI DESA ADAT SANUR - Putu Intan Arianto; Ni Wayan Yuniasih; Ni Luh Putu Netria Febriyanti; Ni Kadek Mayang Sari Dewi; Ni Putu Dinda Dewi (Dharma Bhakti, 2024)
Desa Adat Sanur has the potential for natural resources in the form of abundant fish, but the utilization of these natural resources to increase selling value is still not optimal because the fish is sold raw without any processing. In addition, the potential of Desa Adat Sanur is also a strategic tourism object, with this potential certainly having an impact on Micro, Small and Medium Enterprises (MSMEs) around Desa Adat Sanur. However, there are still many business actors who still combine their business money with their personal money and have not kept financial records so that business profits are also not recorded. Based on these problems, socialization of Micro, Small and Medium Enterprises related to increasing selling value and financial recording is important even though it is simple. This village project activity has solutions related to the problems previously described. The method used in this village project is in the form of socialization and mentoring regarding fish processing into finished products in the form of crackers, product packaging, product labels and making simple financial reports for Micro, Small and Medium Enterprises (MSMEs). The results of this village project can provide an understanding of the importance of recording good financial statements and provide an explanation of how to increase the selling value of fish through the processing of raw fish products into finished products in the form of fish crackers.